Inflammatory Myofibroblastic Tumor in Bladder with Multiple Vesicocutaneous Fistula in Pediatric Patient: A Rare Case Report - Setiawan, Deni; Sari, Puspita P.; Adibrata, Audy S. P.; Nugraha, Harry Galuh; Soetikno, Ristaniah D.; Hernowo, Bethy (Open Access Macedonian Journal of Medical Sciences, 2022)
Inflammatory myofibroblastic tumor (IMT) is a rare tumor that occurs at any age from childhood to late adulthood and may have a slight male predilection. A 7-year-old female presented with gross hematuria and a lump in the lower abdomen since 1 month prior to admission. The complaints were also accompanied by weight loss, abdominal pain and anemia. Ultrasound examination, Cystography, CT-Scan and MRI showed that mass in the bladder. Histopathology examination confirmed diagnosis for IMT, thus, radiology plays an important role in supporting histologic examination for diagnosis and evaluation of IMT.